Enhancement of chemical stability and transdermal absorption of salmon calcitonin loaded in elastic niosomes - Manosroi A. (2014)
Chemical stability and rat skin transdermal absorption by Franz diffusion cells at 6 hours of calcitonin loaded in elastic and non-elastic niosomes were compared with calcitonin solution. Calcitonin loaded in non-elastic niosomes (Tween 61/cholesterol (CHL) at 1:1 molar ratio) and elastic niosomes (Tween 61/CHL/sodium cholate (NaC) at 1:1:0.1 molar ratio) showed higher chemical stability than calcitonin in solution of 16.58 and 18.43 times at 27±2°C and 15.34 and 18.43 times at 45±2°C for 4 weeks, respectively. The half-lives of calcitonin loaded in elastic niosomes were more than calcitonin solution of 41.62 and 8.20 times at 27±2 and 45±2°C while, calcitonin loaded in non-elastic niosomes showed 36.65 and 7.03 times at 27±2 and 45±2°C, respectively. Calcitonin loaded in elastic niosomes gave the accumulate amount of 0.337 mg/cm 2 in the receiving solution more than calcitonin in solution of 1.36 times. Both calcitonin loaded in elastic and non-elastic niosomes did not only show higher chemical stability at high storage temperatures, but also superior transdermal absorption in comparing to calcitonin in solution which can be further developed as a potential topical delivery. © 2012 American Scientific Publishers All rights reserved.